An integrative review of nurses' prosocial behaviours contributing to work environment optimization, organizational performance and quality of care. (22nd April 2018) - Feather, Janice; McGillis Hall, Linda; Trbovich, Patricia; Baker, G. Ross
Abstract : Aim: To rigorously review the literature on the prosocial workplace behaviours of nurses. Background: Prosocial workplace behaviours, predominantly organisational citizenship behaviours have been theoretically and empirically found to promote individual and group level performance in various industries. However, little consensus exists in the literature regarding the impact of nurses' workplace behaviours on the work environment and organisational performance. Evaluation: An integrative literature review was conducted on studies between 1980 and 2016. Nineteen articles were included related to nurses' prosocial behaviours and performance. Results: A positive relationship was noted between workplace behaviours and individual level performance and unit level performance. Albeit multifactorial, leadership and the social structure of the work environment are important factors contributing to the workplace behaviour–performance relationship. Conclusions: Prosocial behaviours influence the social functioning of the work environment and offer insights into the delivery of quality care. Implications for Nursing Management: Nurse managers should recognize the influence of leadership style and characteristics in the work environment that encourage employee participation in prosocial behaviours. These additional voluntary efforts by nursing staff may improve organisational effectiveness and quality of care. Inclusion of these behaviours in performance reviews and as cultural norms may help to foster a more collaborative work environment.